Coding with AI - Minnick, Chris (Hoboken, NJ : John Wiley & Sons, Inc., 2024)
"Coding with AI For Dummies' introduces you to the many ways that artificial intelligence can make your life as a coder easier. Even if you're brand new to using AI, this book will show you around the new tools that can produce, examine, and fix code for you. With AI, you can automate processes like code documentation, debugging, updating, and optimization. The time saved thanks to AI lets you focus on the core development tasks that make you even more valuable. Learn the secrets behind coding assistant platforms and get step-by-step instructions on how to implement them to make coding a smoother process"--
Introduction -- Part 1: Techniques and technologies. How coding benefits from AI -- Parsing machine learning and deep learning -- AI coding tools -- Coding with chatbots -- Part 2: Using AI to write code. Progressing from plan to prototype -- Formatting and improving your code -- Finding and eliminating bugs -- Translating and optimizing code -- Part 3: Testing, documenting , and maintaining code -- Testing your code -- Documenting your code -- Maintaining your code -- Part 4: The part of tens. Ten more tools to try -- Ten AI coding resources -- Index.
Includes index.
"Write more code caster with AI assistance; debug, test, and optimize your code with AI chatbots; use machine learning to speed your process"--Cover.
Keywords: Computer programming; Artificial intelligence; Handbooks and manuals